NIGERIA’S EVOLVING BLUE ECONOMY AND THE SUSTAINABILITY OFARTISANAL FISHERFOLKS LIVELIHOOD - Umehai, Michael Chukwuemeka; Opia, Oji Peter Bonnyface; Abasubong, Kenneth Prudence; Odia, Franklin Ndubuisi; Ejiodu, Patricia Okpohoka (FUDMA Journal of Sciences, 2026)
Nigeria’s evolving blue economy and its potential in increasing the Gross Domestic Product (GDP) and livelihood status of artisanal fisherfolks in the littoral states along the Exclusive Economic Zone (EEZ) is underscored. All benefits derived from the EEZ to the nation’s economy are highlighted, including the advantages and disadvantages of harnessing resources within the EEZ if Maritime Spatial Planning (MSP) is implemented. The vital role of extension, specifically fisheries extension professionals, is emphasized through advocacy, training, and skill acquisition for artisanal fisherfolk inhabitants in the management and conservation of aquatic resources because development interventions would alter the migration, breeding, nursery, and spawning grounds of marine species that transit or inhabit the EEZ. The paper recommends an alignment of policies, linkages, and interagency cooperation by government, non-governmental agencies, professionals, scientists, artisanal fisherfolks, and all stakeholders for the rapid development of Nigeria’s Blue Economy. The coordination and collaboration of all agencies are vital in MSP to achieve the Ministry of Blue Economy mandate. Extension, specifically fisheries extension professionals role in Nigeria’s Evolving Blue Economy, is emphasized in MSP and policy because of fisherfolk livelihoods and the sustainability of aquatic organisms in the EEZ.
Keywords: Blue Economy; Maritime Spatial Planning; Artisanal Fisherfolks; Fisheries Extension; and Exclusive Economic Zone